Probabilistic methods in combinatorial analysis - Sachkov, Vladimir Nikolaevich (Encyclopedia of mathematics and its applications, 1997)
This work explores the role of probabilistic methods for solving combinatorial problems. These methods not only provide the means of efficiently using such notions as characteristic and generating functions, the moment method, and so on, they also allow us to use the powerful technique of limit theorems. The basic objects under investigation are nonnegative matrices, partitions and mappings of finite sets, with special emphasis on permutations and graphs, and equivalence classes specified on sequences of finite length consisting of elements of partially ordered sets; these specify the probabilistic setting of Sachkov's general combinatorial scheme. The author pays special attention to the use of probabilistic methods in order to obtain asymptotic formulae that are difficult to derive using combinatorial methods.